INNOVATIVE TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Mamirova , Gulnoza (Mental Enlightenment Scientific-Methodological Journal, 2024)
The development of modern society requires the informatization of education and poses the task of forming a personality and training a specialist with a sufficient level of professionalism, whose competitiveness in the labor market is now determined not only by his high qualifications in the professional field, but also by his readiness to solve professional problems in the conditions of bilingual communication, ensuring the processes of information interactions. As a result of the transformation of Uzbekistan into an open society, the social status of a foreign language has changed, which has led to an awareness of the importance of mastering it as a tool for orientation in the modern information space, the proficiency of which has become a significant personal and professional characteristic of a specialist. In the article, the author analyzed current trends in the use of pedagogical and information technologies in teaching foreign languages, developed a didactic model for teaching foreign language communication based on the use of Internet technologies, designed a technology for the formation and development of foreign language communication skills and abilities as the main component of a student’s communicative competence